Structural Modification of Sylibin to Derivatives of Sylibin/Hydnocarpin D/Silandrin, and Evaluation of their Cytotoxicity against Cancer Cells - Maihesuti, Liwaliding; Gao, Hongwei; Wang, Qi; Cao, Jianguo; Aisa, Haji A.; Huang, Guozheng (Current Topics in Medicinal Chemistry, 2021)
Background: Flavonolignans like silybin, hydnocarpin, and siliandrin are a group of natural compounds combining the structural moieties of flavonoid and phenylpropanoid (lignan). Hydnocarpin and silandrin have been less explored because of their trace occurrence in nature. Objective: The present study aimed at chemical conversion of silybin to hydnocarpin and siliandrin. Another objective was to synthesize a series of amide derivatives and biologically evaluate them with regard to their anti-cancer effects. Methods: In order to selectively convert silybin to 23-iodo silybin, 23-iodo hydnocarpin D and 23- iodo isosilandrin, the ratio of Ph3P, imidazole and molecular iodine was meticulously adjusted. These three iodide compounds were converted into amide compounds by chemical transformation. MTT method was applied to evaluate their anti-cancer potency. The binding affinity to related proteins was calculated by molecular docking. Results: A total of 45 new amido-derivatives were synthesized and structurally characterized by NMR and HRMS. Some of them showed moderate to good antiproliferative potency against cancer cells. The activity of compound 10j was further testified by colony formation assay and molecular docking. Conclusion: The synthesis of 23-iodo silybin, 23-iodo hydnocarpin D and 23-iodo isosilandrin from silybin was successfully accomplished by one simple iodination reaction. Some of the amide derivatives of sylibin/hydnocarpin D /silandrin exhibited a remarkable inhibitory effect of proliferation on cancer cells compared to silybin. These results would pave the way for further investigation on the derivatives of flavonolignans for the treatment of cancer.
Keywords: Cytotoxicity